2002
DOI: 10.1074/jbc.m200047200
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Communication between Signal Peptides and the SecA Protein DEAD Motor ATPase Domain

Abstract: SecA, the preprotein translocase ATPase is built of an amino-terminal DEAD helicase motor domain bound to a regulatory C-domain. SecA recognizes mature and signal peptide preprotein regions. We now demonstrate that the amino-terminal 263 residues of the ATPase subdomain of the DEAD motor are necessary and sufficient for high affinity signal peptide binding. Binding is abrogated by deletion of residues 219 -244 that lie within SSD, a novel substrate specificity element of the ATPase subdomain. SSD is essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
107
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(116 citation statements)
references
References 53 publications
8
107
1
Order By: Relevance
“…Using fragments, deletional analysis, and chemical crosslinking of synthetic signal peptides, Economou's group concluded that the region at the base of the PPXD (so-called stem region) serves to bind the signal sequence. 69,89 Results of a FRET-based study with complementary crosslinking approaches also implicated the PPXD (specifically the third Using Signal Peptides to Explore Protein Export 315 helix) in signal sequence binding, 93,95 which is consistent with the early crosslinking studies from Mizushima's lab. 94 We have performed a sequence alignment of 550 SecA proteins, and the region proposed by Musial-Siwek et al 93 has a low conservation score (J. L. Maki and L. M. Gierasch, unpublished observations), raising doubt about whether it serves as a direct binding site for signal sequences.…”
Section: Seca-signal Sequence Recognitionsupporting
confidence: 60%
See 4 more Smart Citations
“…Using fragments, deletional analysis, and chemical crosslinking of synthetic signal peptides, Economou's group concluded that the region at the base of the PPXD (so-called stem region) serves to bind the signal sequence. 69,89 Results of a FRET-based study with complementary crosslinking approaches also implicated the PPXD (specifically the third Using Signal Peptides to Explore Protein Export 315 helix) in signal sequence binding, 93,95 which is consistent with the early crosslinking studies from Mizushima's lab. 94 We have performed a sequence alignment of 550 SecA proteins, and the region proposed by Musial-Siwek et al 93 has a low conservation score (J. L. Maki and L. M. Gierasch, unpublished observations), raising doubt about whether it serves as a direct binding site for signal sequences.…”
Section: Seca-signal Sequence Recognitionsupporting
confidence: 60%
“…They also identified another region that had synergistic effects, and termed it IRA2 and the first segment IRA1. 69,70 IRA2, in fact, is the second helicase domain, which was clear once the crystal structure was available.…”
Section: Seca Is Central To the Bacterial Sec Pathwaymentioning
confidence: 98%
See 3 more Smart Citations